The impact of Ricinus straw on tomato growth and soil microbial community - Zhang, Jingyu; Liu, Minghao; Landry, N’da Brou Jean; Duan, Yaping; Li, Xin; Zhou, Xingang (Frontiers in Microbiology, 2024)
Returning straw can alter the soil microbial community, reduce the occurrence of soilborne diseases, and promote plant growth. In this study, we aimed to evaluate the effects of Ricinus straw on tomato growth and rhizosphere microbial community. We carried out microcosm experiments to investigate the effects of Ricinus straw with different dosages (0, 1, and 3%) on tomato dry biomass and rhizosphere bacterial and fungal communities. The results indicated that the dry biomass of tomato seedlings with 1% addition of Ricinus straw increased by 53.98%. In addition, Ricinus straw also changed the abundance, diversities, and composition of tomato rhizosphere microbial communities. In detail, the addition of 1% Ricinus straw increased the relative abundance of putative beneficial bacteria and fungi in straw decomposition, such as Ramlibacter sp., Azohydromonas sp., Schizothecium sp., and Acaulium sp., and decreased the relative abundance of Fusarium sp. Meanwhile, Ricinus straw inhibited the growth of putative pathogenic microorganisms. The correlation analysis showed that the changes in fungal community operational taxonomic units stimulated by the addition of Ricinus straw may play a crucial positive regulatory role in tomato growth. Finally, the representative fungal strain Fusarium oxysporum f. sp. Lycopersici (FOL), named TF25, was isolated and cultured. We found that Ricinus straw extract inhibited the growth of TF25 in an in vitro experiment with an inhibition rate of 34.95–51.91%. Collectively, Ricinus straw promoted plant growth by changing the rhizosphere microbial community composition and inhibiting FOL growth, which provides new evidence for understanding the improvement of key microorganism composition in improving crop growth and the sustainability of agriculture.